INTERACTION, THE PIVOT AROUND WHICH QUALITY EARLY CHILDHOOD EDUCATION SHOULD REVOLVE: Received: 3rd February 2021; Revised: 12th August 2021, 12th October 2021; Accepted: 9th November 2021 - Oppong Frimpong, Samuel (PUPIL: International Journal of Teaching, Education and Learning, 2021)
This position paper advocates that the extent to which children are involved in the teaching and learning process and their environment determines how much knowledge they can create for themselves. The nature of children’s involvement in teaching and learning is largely couched in interaction. Where meaningful involvement in teaching and learning is achieved, it symbolizes quality teaching and learning. Thus, the most important ingredient in Quality Early Childhood Education (QECE) provision is interaction, referring to the contact between two or more people or a person and an object over a common interest. Interaction being argued to be the means by which an early childhood centre functions on a daily basis, the quality of interaction and instruction young children receive at the ECE centres can make or unmake their later lives. Thus, with interaction in the school, learners can have contact with their peers, manipulate TLMs, participate actively during lesson delivery, and take an active part in every activity. Quality interaction, therefore, shows the extent to which learners can be involved in the content of what they are learning both indoor and outdoor within their environment. Consequently, rich interactive experiences at ECE centre play a key role in children’s optimal development.